High-entropy high-hardness metal carbides discovered by entropy descriptors - Pranab Sarker (Nature Portfolio, 2018)
The overwhelming number of possible high-entropy materials represents a big challenge for predicting their existence. Here, the authors introduce an entropy-forming-ability descriptor capturing the synthesizability of these systems, and apply the model to the discovery of new refractory metal carbides.